The Role of Public Administration in Improving the Quality of Education Services in Primary Schools - Ardhana Januar Mahardhani (Indo-MathEdu Intellectuals Journal, 2023)
Primary education is one of the key foundations in the development of individuals and societies. The quality of education services in primary schools has a significant impact on the intellectual, social and economic development of children, as well as the economic growth of a country. Therefore, the role of public administration in improving the quality of education services in primary schools is a very important aspect in the development of the education system. This study aims to examine the role of public administration in improving the quality of education services in primary schools. This research adopts a qualitative approach through literature analysis, which means that it will investigate and explain information and content sourced from various documents and texts as a basis for analysis between 2008 and 2023. The study results show that the role of public administration in improving the quality of education services in primary schools is significant. Public administration plays a role in policy development, resource allocation, monitoring and evaluation, teacher training, collaboration with related parties, psychosocial support and the adoption of innovation and technology. All these aspects aim to create an educational environment that supports children's growth and development and provides a strong foundation for a brighter future